2006
DOI: 10.1002/pi.2075
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and adhesion behaviors of epoxy resins modified with poly(amine‐quinone)

Abstract: An amine-quinone monomer, i.e. 2,5-bis(4,4 -methylenedianiline)-1,4-benzoquinone (BB), was synthesized by the Michael addition of 4,4 -diaminodiphenyl methane with 1,4-benzoquinone. To evaluate the effect of BB content on the glass transition temperature (T g ) and crosslinking density (ρ) of cured diglycidyl ether of bisphenol A (DGEBA)/BB systems, storage modulus and loss factor measurements were obtained using dynamic mechanical analysis. The mechanical properties of the systems were determined in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The total work of adhesion is reduced to (4)(5)(6)(7)(8)(9) In the particular case such as London's forces across the interface, the work of adhesion is determined because the non-dispersive part becomes zero. The only existence of London interactions at the interface between two adherents leads to G / W L 12 (4)(5)(6)(7)(8)(9)(10) where G is the adhesive strength of the assembly. The only existence of London interactions at the interface between two adherents leads to G / W L 12 (4)(5)(6)(7)(8)(9)(10) where G is the adhesive strength of the assembly.…”
Section: Interface Science and Compositesmentioning
confidence: 99%
See 4 more Smart Citations
“…The total work of adhesion is reduced to (4)(5)(6)(7)(8)(9) In the particular case such as London's forces across the interface, the work of adhesion is determined because the non-dispersive part becomes zero. The only existence of London interactions at the interface between two adherents leads to G / W L 12 (4)(5)(6)(7)(8)(9)(10) where G is the adhesive strength of the assembly. The only existence of London interactions at the interface between two adherents leads to G / W L 12 (4)(5)(6)(7)(8)(9)(10) where G is the adhesive strength of the assembly.…”
Section: Interface Science and Compositesmentioning
confidence: 99%
“…Gutmann also suggested that the free energy of an acidbase interaction could be approximated by a two-parameter equation of the form (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) where DG 12 AB is the Gibbs free energy of the acid-base adduct formation, DN B the donor number of the base, and AN A the acceptor number of the acid. This means that a plot of the DN for a series of donors vs. -DG of their adduct formation with a given acid brings up a straight line, allowing the determination of a A and b A .…”
Section: Gutmann's Numbersmentioning
confidence: 99%
See 3 more Smart Citations